2008
DOI: 10.3892/mmr_00000055
|View full text |Cite
|
Sign up to set email alerts
|

Single nucleotide polymorphism typing of the human toll-like receptor 4 gene at the 2-kb upstream region of the 5' untranslated region: New enclosure strategy for the risk grouping of poorly-differentiated gastric adenocarcinoma patients

Abstract: Abstract. To date, no enclosure method for risk grouping patients with poorly-differentiated gastric adenocarcinoma has been identified. We examined the relationship between mutations in toll-like receptor 4 (TLR4) and patients with poorly-differentiated gastric adenocarcinoma. Genomic DNA was extracted from the peripheral blood of 38 patients, 20 with well-differentiated and 18 with poorly-differentiated gastric cancer, from 25 patients with colorectal cancer and from 10 healthy volunteers. The polymorphism o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…Recent studies, conducted in several populations, have shown associations between the polymorphisms TLR1 rs5743618 (Ile602Ser) (154), TLR2 −196 to −174del (155158), TLR2 rs3804099 (157), TLR4 rs4986790 (Asp299Gly) (155, 157, 159), TLR4 rs4986791 (Thr399Ile) (160), TLR4 rs10116253 (161), TLR4 rs10983755 (162), TLR4 rs11536889 (+3725G/C) (155), TLR4 rs1927911 (161), TLR5 rs5744174 (158), TLR9 rs187084 (−1486 T/C) (163), and CD14 rs2569190 (−260 C/T) (155, 164167), and risk of GC development in an ethnic-specific manner (Table 1). In addition, three polymorphisms located in the TLR4 mRNA promoter region (sites −2081, −2026, and −1601) and TLR4 Thr135Ala at the leucine-rich repeat (LRR), have been associated with poorly differentiated GC (168, 169). …”
Section: Toll-like Receptors and Helicobacter Pylori-related Gastric mentioning
confidence: 99%
“…Recent studies, conducted in several populations, have shown associations between the polymorphisms TLR1 rs5743618 (Ile602Ser) (154), TLR2 −196 to −174del (155158), TLR2 rs3804099 (157), TLR4 rs4986790 (Asp299Gly) (155, 157, 159), TLR4 rs4986791 (Thr399Ile) (160), TLR4 rs10116253 (161), TLR4 rs10983755 (162), TLR4 rs11536889 (+3725G/C) (155), TLR4 rs1927911 (161), TLR5 rs5744174 (158), TLR9 rs187084 (−1486 T/C) (163), and CD14 rs2569190 (−260 C/T) (155, 164167), and risk of GC development in an ethnic-specific manner (Table 1). In addition, three polymorphisms located in the TLR4 mRNA promoter region (sites −2081, −2026, and −1601) and TLR4 Thr135Ala at the leucine-rich repeat (LRR), have been associated with poorly differentiated GC (168, 169). …”
Section: Toll-like Receptors and Helicobacter Pylori-related Gastric mentioning
confidence: 99%